Teknologi Aplikasi Asap Cair Grade 3 Tempurung Kelapa Terhadap Kualitas Kayu Meranti - Alamsyah; Abrina Anggraini, Sinar Perbawani; Yuniningsih, Susy (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2020)
Liquid smoke can be obtained by condensing the smoke resulting from the pyrolysis chimney. Liquid smoke resulting from the pyrolysis process can be used as raw material preservatives, antioxidants, etc. Grade 3 liquid smoke is suitable for wood preservation and can also be used as a latex coagulant. In this study, it aims to determine what percentage of liquid smoke concentration is optimal for the preservation of meranti wood and determine the optimal soaking time of the meranti wood preservation process, the method used for the data retrieval process which is the measurement of acid content and the number of bacteria. The tool used is a series of pyrolysis tools. The acidity of meranti wood samples that are not soaked using liquid smoke is generally very high starting from 6Â±10, while for meranti wood samples soaked acidity levels are 5-6. The lowest bacterial mortality percentage (36.4%) control while the highest mortality percentage reaches 92%-100% indicated in the concentration of treatment. At a concentration of 25% able to inhibit bacterial attacks, it can be seen with a mortality percentage of 100% of all pyrolysis temperature levels. Liquid smoke retention at a concentration of 35% is the highest and more effective at immersion for 4 hours compared to the immersion of 3, 5, and 6 hours. Liquid smoke added to Meranti wood has toxic power to bacterial development. At a concentration of 35%, the average weight loss percentage of the test sample was 27.36%.